CFD modeling of orthogonal wave-current interactions in a rectangular numerical wave basin - Kai Wei; Kaiyu Hu (Advances in Bridge Engineering, 2024)
Abstract Sea-crossing bridges are subject to long-term simultaneous wave and current loadings throughout thier life cycle. The wave-current interaction makes the hydrodynamic load calculation difficult and challenging, especially in simulating the noncollinear wave-current interactions between waves and currents due to potential disturbances such as wall reflections within the observational zone. Therefore, in this study, a numerical flume was built based on the Reynolds time-average (RANS) equation and k-ε turbulence model using the computational fluid dynamics (CFD) software Flow-3D to investigate noncollinear wave-current interaction numerical simulation methods. The collinear wave-current interactions were then numerically simulated using the inflow boundary and mass source wave generation method, and the developed numerical flume was validated with experimental results based on a large-scale wave-current flume. Furthermore, a three-dimensional numerical simulation of complex noncollinear wave-current interactions was developed. The developed rectangular numerical basin based on the collinear wave-current flume was validated with theoretical results regarding wavelength variations in a noncollinear wave-current interaction field. Finally, the effective observation zone of orthogonal wave-current interactions was explored. This study is important for advancing bridge hydrodynamic research into noncollinear wave-current interactions.